Human-information interaction and technical communication : concepts and frameworks 2026-02-15T18:22:07+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Albers, Michael J. (Information Science Reference, 2012)

(untitled)
"This book works to provide practical knowledge based on a sound theoretical foundation for allowing people to engage in a meaningful dialogue as they make decisions with respect to designing that communication"--Provided by publisher